(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Design and development of herbal nanoparticles has become a frontier research in the nanoformulation arena. To update researchers, an attempt has been made to review nanoformulation-based herbal patents. This article mainly covers herbal medicines are used for the treatment of cardiovascular diseases, Parkinsonism, pulmonary diseases, proliferative diseases, Alzheimer’s disease, diabetes, cancer therapy, anti-osteoporosis, and the like. It has been revealed that nanoparticles of Curcumin have been widely designed to increase its bioavailability and for treatment of cancers like breast cancer, lung cancer, pancreatic cancer, and so on. The common nanoformulated herbal medicines are Panax ginseng, Curcuma longa, Silybum marianum, Withania somnifera, Gymnema sylvestre, Salvia miltiorrhiza, and the like, having a profound future potential.